ESTETIKA VISUAL DAN NONVISUALKOIN CINA KUNO ASLI YANG DITEMUKAN DI BALI DAN KOIN CINA BUATAN LOKAL - Tjokorda Udiana Nindhia Pemayun Pemayun; Tjokorda Gde Tirta Nindhia Nindhia (Fakultas Sastra Universitas Negeri Malang, 2011)
Up to now, Balinese culture and art cannot be separated from the utiliza- tion of old Chinese coins which local people in Bali call pis bolong. The use of those old Chinese coins in traditional ritual in Bali is found even from the infants until the end of that person’s life at cremation ceremony. The cremation ceremony uses the Chinese old coins to be burned with the deceased and to be sent with the ash from the burned deceased into the sea. This practice makes the number of old Chinese coins decrease meanwhile the demand of using the coins increase. The condition is worsened by the practice of using old Chinese coins as souvenirs. The local metal craftsmen have tried to solve the scarcity of the coins by producing a local-made Chinese coins and making them as similar as the original Chinese coins. However, due to the lack of local craftsmen’s aesthetics assessment visually and non-visually on old Chinese coins, their physical appearances were very much different from its original Chinese coins. Therefore, this paper presents the result of the observation of aesthetics assessment visually and non-visually on old Chinese coins that can be used as guidance to produce local-made old Chinese coins as similar as its original.